ʺThe role of the educational environment in the civic education of schoolchildrenʺ - Bilash, Ya. (Problems of Engineer-Pedagogical Education, 2024)
The article analyses the approaches of scholars to the interpretation of the concept of "civic education" of schoolchildren. The features of the complexity of the educational process that affect the complexity of its organisation are described. It has been established that civic education in Ukraine has received different attention at different stages of the State's development. The government policy in defining the goal is crucial for its provision. Based on the analysis of the definitions of scholars, civic education is characterised as a process of forming citizenship - an integrated quality of a personality that enables a person to feel morally, socially, politically and legally capable and protected. The processes of decentralisation of government and state institutions in Ukraine have led to changes in civic education, making it more understandable and concrete. Civic education is education in the community as the closest environment of the individual. It is determined that along with the student's family, the educational environment, to which the student belongs as a subject, plays an important role in civic education. Educational institutions as social institutions have always performed the tasks of the government policy in the field of education of the younger generation. The educational environment in an educational institution is characterised as a complex phenomenon that includes physical, social, psychological and educational aspects. At the present stage, taking into account the situation in Ukraine, the features and priority ways of ensuring aspects of the educational environment are identified. Given the impact of the educational environment on the social education of schoolchildren, certain components of the content of the process are identified with an emphasis on the area under study - civic education of schoolchildren. The result of civic education of schoolchildren in accordance with the competence approach is the formed civic competence. In accordance with the defined sequence of the process, it is important to ensure the passage of the following stages: 1) introduction into the content of the educational process of knowledge related to civic education (history and national values, cultural traditions, language and heritage, European standards and values (humanism, freedom, equality, justice); 2) creation of conditions for the formation of values of awareness of being a citizen of a particular country in students on the basis of this knowledge; 3) development of skills of active citizenship (participation in public activities). The peculiarities of ensuring each of the stages in accordance with modern conditions are revealed. The forms and methods that are appropriate to use in the civic education of schoolchildren in the educational environment are determined.